2013
DOI: 10.2217/ijr.13.19
|View full text |Cite
|
Sign up to set email alerts
|

Sources of pain in osteoarthritis: implications for therapy

Abstract: Osteoarthritis is the leading musculoskeletal cause of disability in western society. Despite this, it is still difficult to gain a precise definition of what osteoarthritis actually is. It is well known that there is a modest correlation between x-ray changes and pain. However, for knee joint structure there is largely consistent evidence that bone marrow lesions, synovitis/effusions and cartilage defects are associated with knee pain and cartilage loss. In addition, muscle strength and obesity predict pain e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…It is well known that there is a modest correlation between X-ray changes and pain. However, for the knee joint structure, there is largely consistent evidence that bone marrow lesions, synovitis/effusions and cartilage defects are associated with knee pain and cartilage loss [1]. Thus, it would seem logical to regard knee (and perhaps other forms of) OA as an umbrella term for a number of different pathological processes that result in cartilage loss.…”
Section: Overview Of Osteoarthritis and Its Current Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that there is a modest correlation between X-ray changes and pain. However, for the knee joint structure, there is largely consistent evidence that bone marrow lesions, synovitis/effusions and cartilage defects are associated with knee pain and cartilage loss [1]. Thus, it would seem logical to regard knee (and perhaps other forms of) OA as an umbrella term for a number of different pathological processes that result in cartilage loss.…”
Section: Overview Of Osteoarthritis and Its Current Treatmentsmentioning
confidence: 99%
“…Its prevalence is increasing markedly because of an ageing population [1]. In all, 10 % of the world's population aged 60 years or older have pain or disability from OA [2].…”
Section: Introductionmentioning
confidence: 99%
“…A more recent study suggested the association was also independent of large osteophytes, marked synovitis and macerated meniscal tears suggesting damaged articular cartilage may independently lead to knee pain . This may be mediated by substance P nociceptive fibres, superinduction of cyclooxygenase 2 and prostaglandins or increased load on subchondral bone . Cartilage defects can heal (albeit at low rates after age 45), predict cartilage loss in multiple studies and risk of knee replacement in two studies .…”
Section: Cartilage Defectsmentioning
confidence: 99%
“…There is strong human evidence that bone plays an important role in the pathogenesis of osteoarthritis . One of these features, BML, has been recognised as a key component of knee osteoarthritis . A number of studies have linked BML with knee pain.…”
Section: Bmlmentioning
confidence: 99%
See 1 more Smart Citation